Open wounds : the crisis of Jewish thought in the aftermath of the Auschwitz - Patterson, David 1948- (Pastora Goldner series in post-Holocaust studies, 2006)
Introduction : the open wounds of Jewish thought -- The bankruptcy of modern and postmodern thought -- Ethical monotheism and Jewish thought -- The Holocaust and the Holy Tongue -- The sifrei kodesh and the Holocaust -- The Muselmann and the matter of the human being -- Jewish thought and a post-Holocaust tikkun haolam -- Mystical dimensions of post-Holocaust Jewish thought -- Though the Messiah may tarry -- Conclusion : no closure